Central condylar displacement with brain abscess from chronic mandibular osteomyelitis. (11th January 2013) - Lee, Thomas; Green, Ross; Hsu, Jack
Abstract : In this case report, we describe a unique long‐term complication from undiagnosed mandibular osteomyelitis. A 53‐year‐old female who underwent a dental extraction complicated by chronic postoperative odontogenic infection and cutaneous parotid fistula formation 2 years earlier presented with acute mental status change, gradual unilateral facial nerve palsy (House‐Brackmann score V), and nontraumatic dislocation of the condylar head into the middle cranial fossa. The patient's chronic mandibular osteomyelitis led to glenoid fossa erosion, middle cranial fossa penetration, and temporal lobe abscess formation. A combined middle cranial fossa approach through a burr hole placed in the squamous temporal bone near the zygomatic root and intraoral mandibular approach to ipsilateral condylar head was performed to complete partial mandibulectomy, including condylectomy. The patient was treated with 6 weeks of meropenem perioperatively. Four months after the surgery, the patient had complete resolution of skull base osteomyelitis, parotid fistula, and neurologic deficits and full recovery of facial nerve function (House‐Brackmann score of I)